THE IMPACT OF CAPITAL STRUCTURE ON FIRM VALUE WITH PROFITABILITY AS A MODERATING VARIABLE: EVIDENCE FROM CONSUMER GOODS COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Benni Sumarman; Etty Sri Wahyuni (RADJA PUBLIKA, 2026)
This study investigates the impact of capital structure on firm value with profitability as a moderating variable in consumer goods companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. Utilizing signaling theory and trade-off theory as the theoretical framework, this research examines whether the relationship between capital structure and firm value is contingent upon the level of profitability. The sample comprises 35 consumer goods companies selected through purposive sampling, resulting in 175 firm-year observations. Capital structure is measured using Debt to Equity Ratio (DER), firm value is proxied by Price to Book Value (PBV), and profitability is measured using Return on Assets (ROA). The analytical method employed is Moderated Regression Analysis (MRA) with panel data regression using EViews 13. The findings reveal that capital structure has a significant negative effect on firm value. Furthermore, profitability significantly strengthens the negative relationship between capital structure and firm value. These results suggest that highly profitable firms experience greater value deterioration when employing higher leverage. The findings contribute to the existing literature by providing empirical evidence on the moderating role of profitability in emerging market contexts and offer practical implications for corporate financial decision-making.